Combination of Hot Forming with CRP and Rapid Cooling to Obtain Enhanced Formability in Thermomechanical Treatment. (15th February 2017) - Birnbaum, Peter; Baumann, Markus; Kunke, Andreas; Kraeusel, Verena; Landgrebe, Dirk
ABSTRACT: In sheet metal forming, rapid cooling of austenitized steel and CRP (cushion-ram pulsation) results in an optimized formability. An analysis is conducted regarding the influence of a stepwise deep drawing process of manganese-boron steel 22MnB5, using an oscillating ram-cushion motion at simultaneous cooling. The stops occurring in stepwise forming provide sufficient time for softening and recovery of forming properties. The microstructure can be adjusted by controlled cooling. In order to examine the newly developed process in more detail, FE simulation is applied. Thus, relevant process and material parameters can be determined. The considered values are required for profound experiments using the forming simulator BAEHR DIL 805 A/D. The softening behavior at defined forming temperatures due to CRP are examined. The experimental results of softening at distinctive temperatures provide a basis for the combined processes of stepwise hot sheet metal forming and simultaneous cooling.